ACUTE RHEUMATIC FEVER IN THE 21st CENTURY: THE PROBLEM THAT CANNOT BE FORGOTTEN - N. N. Kuzmina; B. S. Belov; L. G. Medyntseva (Научно-практическая ревматология)
Despite considerable advances in the control of acute rheumatic fever (ARF), the problem of this disease remains relevant and contains a number of unsolved issues as before. The paper displays an epidemiological update on ARF and analyzes a number of provisions of the recent (2015) American Heart Association guidelines on the revision of the Jones diagnostic criteria. The wide discussion in the academic circles concerns the clinical aspects of ARF (carditis, chorea), an understanding of which makes it possible to correctly predict the course of the disease, but also to form a rational therapy policy that affects its outcome. Current approaches to primary and secondary prevention of ARF are given; emphasis is placed on the necessity of designing a novel vaccine against Streptococcus.